(untitled) (Research, Society and Development, 2022)
Objective: To analyze the mental health of the LGBTQIA+ population in the face of the COVID-19 pandemic. Methods: This is an integrative review carried out in six stages. Data collection was carried out on the VHL, SciELO and LILACS platforms in July 2022, including studies from the last two years. Results: 85 studies were obtained, but after the established criteria, 21 were selected to compose the final sample. There was an increase in the rate of mental disorders in LGBTQIA+ people, such as stress, depression, anxiety, anguish, fatigue, loneliness, family conflicts, use of psychotropic drugs and financial difficulties. This fact is worrying, since this population already had a greater number of mental disorders, due to prejudice, vulnerability and social stigma, which was worsened by isolation. Lesbian and transsexual women become more prone to mental illness due to the accumulation of stigmas related to gender and sexual orientation and a lower perception of social support. Conclusion: The LGBTQIA+ population did not always have adequate social and health support, given the historical reality of prejudice and discrimination to which they were and are subjected. Further studies on the impacts on mental health as a result of COVID-19 are suggested, in view of the scarcity of works.